Super-rapid quantitation of the production of HIV-1 harboring a luminescent peptide tag - Ozono, Seiya; Zhang, Yanzhao; Tobiume, Minoru; Kishigami, Satoshi; Tokunaga, Kenzo (The Journal of biological chemistry, 2020)
In studies of HIV-1, virus production is normally monitored by either a reverse transcriptase assay or a p24 antigen capture ELISA. However, these assays are costly and time-consuming for routine handling of a large number of HIV-1 samples. For example, sample dilution is always required in the ELISA procedure to determine p24 protein levels because of the very narrow range of detectable concentrations in this assay. Here, we establish a novel HIV-1 production assay system to solve the aforementioned problems by using a recently developed small peptide tag called HiBiT. This peptide is a fragment of NanoLuc luciferase and generates a strong luminescent signal when complemented with the remaining subunit. To employ this technology, we constructed a novel full-length proviral HIV-1 DNA clone and a lentiviral packaging vector in which the HiBiT tag was added to the C terminus of the integrase. Tagging the integrase with the HiBiT sequence did not impede the resultant virus production, infectivity, or susceptibility to an integrase inhibitor. EM revealed normal morphology of the virus particles. Most importantly, by comparing between ELISA and the HiBiT luciferase assay, we successfully obtained an excellent linear correlation between p24 concentrations and HiBiT-based luciferase activity. Overall, we conclude that HiBiT-tagged viruses can replace the parental HIV-1 and lentiviral vectors, which enables us to perform a super-rapid, inexpensive, convenient, simple, and highly accurate quantitative assay for HIV-1/lentivirus production. This system can be widely applied to a variety of virological studies, along with screening for candidates of future antiviral drugs.